Broiler management practices for small-scale farmers and their impact on growth performance - Ndlovu, Sithembisile (My University, 2026)
The broiler management practices that were likely to be neglected by small-scale farmers and their effects on broiler growth were investigated. For the management practice study, small-scale broiler farmers who reared 4,000 birds or fewer were targeted. The study investigated 100 farmers in the Bushbuckridge Local Municipality. An exploratory study was conducted to identify the broiler management practices employed by small-scale farmers. A structured questionnaire was used. The collected data included household information on type, ethnic group, marital status, and occupation. The farmers' information included the enterprise’s location, age, gender, education level, farming experience, their farming practices, and standard broiler management techniques. Management practices included the number of broiler houses and their carrying capacities, the number of birds housed, the application of an all-in, all-out rearing strategy, rest periods for the broiler house(s), a vaccination programme, management of sick birds, record-keeping, and waste disposal. Foot bath, feed and water wastage, adjustability of feeders and water troughs, number of feeders and water troughs, heating system, ventilation system, and bedding (colour, wetness, and compactness) were observed during farm visits. The sizes of broiler houses and the depth of the litter were measured. Data was coded for analysis purposes. Data on vaccination, footbath, all-in-all-out, drinkers' and feeders' adjustments, stocking rate, bedding height, house resting, and broiler-to-equipment ratios (per drinker and per feeder) were categorised into adherence and non-adherence/neglect to management practices. The Statistical Package for the Social Sciences/SPSS (IBM Corp., 2023), Version 29.0.0.0 (241), was used to analyse the data. There were 47% female-headed and 53% male-headed households. Sixty-nine percent of farmers were single, 24% were married, and 7% were widowed. The prevalence of male (51%) and female (49%) farmers was quite similar. Youth farmers made up 53%. Farmers had 13% primary, 40% secondary, and 47% higher education. Sixty-five percent of farmers had less than 5 years of farming experience, while the remainder had more. Agriculture: 60% of farmers earned their living solely from farming, whereas 40% earned it from both on-farm and off-farm sources. Most (68%) enterprises were in rural areas. In terms of capacity, most farmers had a single broiler house (74%), and houses that could accommodate 100-500 birds were most common (76%). Most farmers adhered to management practices of stocking rate (94%), house resting (81%), vaccination (94%), all-in and all-out strategy (90%), bird drinker and feeder (equipment) ratio (76%), and equipment adjustment (90%). The two management practices that farmers most neglected were bedding height (96.4%) and foot baths (85%). Overall, the most concurrently neglected practices were adequate resting of the broiler house, adequate bedding, and footbath (57%). For the determination of the effects of the neglected standard management practices on growth performance study, thirty (30) small-scale broiler farmers were purposively sampled. The management strategies investigated and the number of enterprises sampled were: 0 = adhering to the five key management practices (7); 1 = inadequate resting of the house and bedding, and no footbath (7); 2 = inadequate resting of the house and bedding, and no footbath (7); 3 = inadequate bedding and no footbath (7), and 4 = inadequate resting of the house and bedding, no footbath and vaccination, and heights of drinkers and feeders not adjustable (i.e., neglect of the five key managerial practices) (n = 2). A single broiler house, stocked with day-old chicks, was targeted per farmer. Observation tools (record sheet and measurements) were used to collect data for broiler numbers, body weight, mortality, and feed offered. Researchers weighed birds on days 8, 22, and 36. Data were subject to Independent-Samples Kruskal-Wallis Tests in SPSS. Differences in distributions across the management practices were compared, and significance values were adjusted by the Bonferroni correction for multiple tests. Weight gain days 8-21 and day 21 weight were higher (P<0.05) for Strategies 0 (52 ± 8.2 g/b/d and 913 ± 120.0 g) and Strategy 3 (50 ± 5.8 g/b/d and 880 ± 88.7 g) than for Strategy 4 (28 ± 4.1 g/b/d and 548 ± 62.2 g). Fewest broilers died under Strategy 0 (8 ± 6.0), some under Strategies 1 (23 ± 15.1) and 3 (11 ± 8.0), and many under Strategy 4 (45 ± 12.0) during days 1-35. Neglecting house rest and vaccination practices led to poor performance under Strategy 4. Key stakeholders should prioritise these two practices for broiler farming to contribute to poverty eradication and income generation for all.
AGMAAS
Department of Animal Science
Keywords: Adherence to practices; UCTD; Demography; Exploration farm visits; Bird mortality; Winter season; Rural areas; 338.47664930968257; Farms, Small -- South Africa -- Limpopo; Chickens -- South Africa -- Limpopo; Broilers (Poultry) -- South Africa -- Limpopo